2021
DOI: 10.3390/su13010399
|View full text |Cite
|
Sign up to set email alerts
|

Research on Speeds at Roundabouts for the Needs of Sustainable Traffic Management

Abstract: Knowledge of the characteristics of speed at roundabouts is very important in design procedures, simulation models, and determining the influence of these roundabouts on traffic conditions in a street network. Sustainable management in the street network means the influence of all its parts on traffic conditions and travel time. In order to reliably determine roundabouts parameters in the procedures of planning and the choice of sustainable method of traffic management, it is very important to know the values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The results of this part of the research indicated that for the analyzed roundabouts even a small change in the deflection around the central island had an influence on the noise levels generated by road traffic. Namely, the results showed that the decrease in deflection around the central island caused the increase in design speed on the fastest path segments on the entry, exit, and around the central island, which is in line with the previous studies on the vehicle speed on roundabouts [33,74,75]. The impact of this design speed increase on modeled noise levels was negligible until the median speed deviations reached 6 km/h (deflection decrease of 4 m).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this part of the research indicated that for the analyzed roundabouts even a small change in the deflection around the central island had an influence on the noise levels generated by road traffic. Namely, the results showed that the decrease in deflection around the central island caused the increase in design speed on the fastest path segments on the entry, exit, and around the central island, which is in line with the previous studies on the vehicle speed on roundabouts [33,74,75]. The impact of this design speed increase on modeled noise levels was negligible until the median speed deviations reached 6 km/h (deflection decrease of 4 m).…”
Section: Discussionsupporting
confidence: 89%
“…To achieve a required reduction in noise levels, it is necessary to match the physical layout of the road to the intended speed and to provide as smooth a driving pattern as possible [20]. Modern roundabout, as a traffic calming device on which operating speed depends on the geometry (deflection around the circular island) [32,33], and a device that can carry smooth traffic flow by minimizing the start-stop operations of drivers, fulfills the abovementioned requirements for the effective noise abatement measure.…”
mentioning
confidence: 99%
“…Recent studies have concentrated on impact assessment in the "smart roundabout" domain (see Figure 1) and have delved into the potential of incorporating smart technologies into existing or planned roundabouts [14,15]. The goal is to leverage the benefits of integrating cutting-edge technological advancements into these infrastructures to fulfill the needs of sustainable traffic management [99]. Although not aiming for exhaustive coverage but rather to highlight key issues amenable to a common analytical approach, a search was conducted in the Scopus database, focusing solely on the term 'smart roundabout' within a 'title, abstract, and keywords' search.…”
Section: Where Is the Research On Smart Roundabouts Headed?mentioning
confidence: 99%
“…Traffic congestion can also be assessed from the graph theoretical perspective: for example, it has been established that the centrality properties of a street network strongly correlate with vehicular density [8,9]. The importance of identifying key structural points in the network is therefore fundamental to the design and application of infrastructural solutions, such as roundabouts [10][11][12] and overpasses [13,14], aiming to ensure a smooth flow of vehicles.…”
Section: Introductionmentioning
confidence: 99%